Chinese and Russian Perspectives on Globalization and Regionalization and the Implications for Eurasian Integration - W. Dai (Сравнительная политика, 2025)
Great powers play an important role in global and regional processes. In the context a shift towards deglobalization among Western countries, China and Russia are maintaining their positions on economic globalization and implementing their ideas to advance Eurasian integration. The objective of this study is to analyze and compare the Chinese and Russian perspectives on globalization and regionalization, and to examine the implications for Eurasian integration. Based on a comparison of the official positions and expert views of the two countries, the author came to the conclusion that despite some differences in Chinese and Russian views, they share common positions on two important matters of globalization and regionalization: globalization should be beneficial to all humanity, and regional integration does not contradict globalization. This provides the basis for cooperation between the two countries in the Eurasian integration processes - the SCO, the EAEU and the BRI.